The prophylactic effects of monoclonal antibodies targeting the cell wall Pmt4 protein epitopes of Candida albicans in a murine model of invasive candidiasis - Wang, Xiaojuan; Liu, Peng; Jiang, Yuanying; Han, Bing; Yan, Lan (Frontiers in Microbiology, 2022)
Candida albicans (C. albicans) is the most prevalent opportunistic human pathogen, accounting for approximately half of all clinical cases of candidemia. Resistance to the existing antifungal drugs is a major challenge in clinical therapy, necessitating the development and identification of novel therapeutic agents and potential treatment strategies. Monoclonal antibody-based immunotherapy represents a promising therapeutic strategy against disseminated candidiasis. Protein mannosyltransferase (Pmt4) encodes mannosyltransferases initiating O-mannosylation of secretory proteins and is essential for cell wall composition and virulence of C. albicans. Therefore, the Pmt4 protein of C. albicans is an attractive target for the discovery of alternative antibody agents against invasive C. albicans infections. In the present study, we found that monoclonal antibodies (mAbs) C12 and C346 specifically targeted the recombinant protein mannosyltransferase 4 (rPmt4p) of C. albicans. These mAbs were produced and secreted by hybridoma cells isolated from the spleen of mice that were initially immunized with the purified rPmt4p to generate IgG antibodies. The mAbs C12 and C346 exhibited high affinity to C. albicans whole cells. Remarkably, these mAbs reduced the fungal burden, alleviated inflammation in the kidneys, and prolonged the survival rate significantly in the murine model of systemic candidiasis. Moreover, they could activate macrophage opsonophagocytic killing and neutrophil killing of C. albicans strain in vitro. These results suggested that anti-rPmt4p mAbs may provide immunotherapeutic interventions against disseminated candidiasis via opsonophagocytosis and opsonic killing activity. Our findings provide evidence for mAbs as a therapeutic option for the treatment of invasive candidiasis.